NILAI TUKAR, INFLASI, NET PROFIT MARGIN (NPM), DEBT TO EQUITY RATIO (DER), DAN HARGA SAHAM - Zerlinda Chindarani Ficsanes; Noordiyati; Jakiroh; Wahyuddin; Hilmi, Rahmat; Darnida, Yondi Caturadina (Jurnal Ilmiah Ekonomi Bisnis, 2022)
This research aims to determine and analyze the significant influence of exchange rates, inflation, Net Profit Margin (NPM), Debt To Equity Ratio (DER) on share prices in telecommunications companies listed on the Indonesia Stock Exchange (BEI). This research is correlational research that uses multiple linear regression methods to test hypotheses. The research results in this study show that the exchange rate, inflation, NPM and DER simultaneously influence stock prices. Exchange rates, inflation, share prices and NPM partially do not have a significant effect on share prices, while DER has a significant effect on share prices. DER has the most dominant influence on share prices because the company's funding strategy uses debt to reduce the tax burden. Apart from that, telecommunications companies provide products that are really needed by the public to meet their daily needs, so it is believed that their sales targets can be achieved. It is hoped that the results of this research can be input for investors in making investment decisions regarding macroeconomic factors and share fundamentals in telecommunications companies listed on the IDX. A company with good financial results is easy to develop because sufficient funds are available for the company's business operations. By analyzing financial figures, investors can get signals to decide whether to invest in the company they want. Keywords: Exchange Rate, Inflation, Net Profit Margin (NPM), Debt To Equity Ratio (DER), Stock Prices